Improved osteointegration response using high strength perovskite BaTiO3 coatings prepared by chemical bath deposition. (February 2023) - Sanaullah, Ifra; Khan, Hera N.; Sajjad, Amna; Khan, Sidra; Sabri, Anjum N.; Naseem, Shahzad; Riaz, Saira
Abstract: A wide range of bioactive materials have been investigated for tissue engineering and regeneration. Barium titanate is a promising smart material to be used as scaffold for bone tissue engineering. Barium titanate coatings are prepared in the present study using chemical bath deposition technique. Coatings are prepared at room temperature with the variation in solution molarity from 0.1 to 1.2 M. Perovskite tetragonal phase is observed after annealing the samples at 300 °C using 1.0–1.2 M solutions. Normal-anomalous dielectric response is observed for annealed coatings. Maximum transmission of ∼55% and ∼82% is observed under as-prepared and annealed coatings, respectivly. Variation in direct band gap, i.e. 3.45–3.64 eV, is observed with varying molarity. High hardness of the coatings (∼1180 HV) is observed at 1.2M with fracture toughness of ∼22 MPam −1/2 . Biodegradation studies show smaller values of weight loss even after immersion in simulated body fluid (SBF) after 26 weeks. Barium titanate coatings also show high antioxidant activity. BaTiO3 's antibacterial reaction is evaluated against microorganisms such as Escherichia coli ( E. coli ) and Staphylococcus aureus . Antibacterial activity shows highest zone of inhibition (∼31 mm) against Staphylococcus aureus bacteria. Quantitative real-time PCR is used to assess the gene expression profile in cultivated cells. Thus, coatings produced without the use of hazardous solvents/reagents utilizing CBD technique are a potential material for biomedical applications. Graphical abstract: Image 1 Highlights: Chemical bath deposition was used to fabricate coatings of barium titanate by changing molarity of the sols ranging from 0.1 M to 1.2 M. Tetragonal perovskite BaTiO3 along with direct band gap and high value of hardness was observed for 1.0 M to 1.2 M based coatings after annealing at 300 °C. High antioxidant and antimicrobial activity with low hemolytic activity was observed for optimized coatings of BTO. VEGF gene expression was considerably greater in the cells with 1.0 M and 1.2 M sample than in the other samples by means of Quantitative real-time PCR gene expression.